Paper book and digital book: a comparative study - abbes, fathi (Journal of Social Sciences and Humanities, 2024)
Reading is considered one of the most important means of acquiring knowledge and information in various topics and fields. It is one of the most important windows to human knowledge through which the individual has access to human thought in the past and present. Through it, a person can develop his intellectual, linguistic and expressive abilities and expand his mental perceptions. And talking about reading leads us to talk about... The book is a tool for practicing reading and about its history and development throughout the ages, starting with writing on rocks, caves, caves, clay tablets, and papyrus scrolls, all the way to paper, which was and still is one of the best materials used to transmit and circulate information, preserve heritage, and transfer it from generation to generation, and from it the paper book appeared, which has become an effective figure. In the development of thought and literature. Despite all this, the paper book lives today in a strong competitive atmosphere with modern technological means, which affected it in terms of form, so it moved from the paper form to the digital electronic form. And therefore this study came to shed light on the practice of the act of reading among the book in its traditional paper form. And its digital form, and to show the similarities and differences between both media or carriers through a comparative descriptive study